Pengembangan LKS pada Materi Cahaya dan Alat Optik dengan Model Inquiry Berbasis Karakter untuk Siswa SMP - Yasinta Embu Ika; Ana Silfiani Rahmawati (Program Studi Pendidikan Fisika STKIP Nurul Huda, 2019)
This research aims to investigate the effect of developing character-based phisic based character inquiry models for junior high school students. This research used the type of Research and Development (R&D) with Quasi Experimental Design in the form of Nonequivalent Control Group Design. The results show: worksheet light and optical instruments based on inquiry models are included in the criteria are very suitable to be used as a study guide for students of class VIII SMP witha presentation on the feasibilityof the worksheet 96,87%; There is a significant difference between the learning outcomes of students who use the Science worksheet light and optical inquiry model character and students who do not use Science worksheet light and optical inquiry model character; The application of the Natural Science worksheet light and optical characterized by the inquiry model can improve students' understanding of the subject matter of light and optical devices. Improved learning outcomes cognitive aspects including the criteria are; and The use of science worksheets light and optical characterized by inquiry models can develop student character that is within the criteria of culture.